Controlling in planta gold nanoparticle synthesis and size for catalysis - Loskarn, Marc; Shamsul Harumain, Zakuan Azizi; Dobson, Jessica A.; Hunt, Andrew J.; McElroy, Con Robert; Klumbys, Evaldas; Johnston, Emily; Sanchez Alponti, Juliana; Clark, James H.; Maathuis, Frans J. M.; Bruce, Neil C.; Rylott, Elizabeth L. (ACS Publications, 2024)
Gold nanoparticles (Au-NPs) are used as catalysts for a diverse range of industrial applications. Currently, Au-NPs are synthesized chemically, but studies have shown that plants fed Au deposit, this element naturally as NPs within their tissues. The resulting plant material can be used to make biomass-derived catalysts. In vitro studies have shown that the addition of specific, short (∼10 amino acid) peptide/s to solutions can be used to control the NP size and shape, factors that can be used to optimize catalysts for different processes. Introducing these peptides into the model plant species, Arabidopsis thaliana (Arabidopsis), allows us to regulate the diameter of nanoparticles within the plant itself, consequently influencing the catalytic performance in the resulting pyrolyzed biomass. Furthermore, we show that overexpressing the copper and gold COPPER TRANSPORTER 2 (COPT2) in Arabidopsis increases the uptake of these metals. Adding value to the Au-rich biomass offers the potential to make plant-based remediation and stabilization of mine wastes financially feasible. Thus, this study represents a significant step toward engineering plants for the sustainable recovery of finite and valuable elements from our environment.